Long term trend analysis of upstream and middle-stream river in Langat Basin, Selangor, Malaysia - Siti Hawa Mohd Yusoff; Firdaus Mohamad Hamzah; Othman Jaafar; Hazrina Tajudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The present study investigates the trend in long term monthly streamflow of Sungai Lui (upstream) and Sungai Kajang (middle-stream) of the Sungai Langat Basin located in Selangor, Malaysia. The Mann-Kendall (MK) and Innovative Trend Method (ITM) tests were utilized to assess the trends at the two stations. The trend free pre-whitening (TFPW) and variance correction (VC) tests were used to assess the effects of serial correlation on the established trend, and Sen’s slope estimator was used to assess the magnitude of streamflow. Based on Sen’s Slope estimator results, the trend magnitude for Lui station is very small compared to the Kajang station. The Kajang station shows the highest increase in trend magnitude for November. The results of TFPW and VC trend tests showed that the most significant increasing trend of months occurred at Kajang station, while the less increasing significant trend of months occurred at Lui station. It can be concluded that similar trend results were obtained when the modified Mann-Kendall and ITM were applied to the same data for Sungai Lui and Sungai Kajang. The study found that there is a significant difference in terms of trend and magnitud between upstream and middle-stream.